Deciphering the clinical features of heterogeneous stage III non-small cell lung cancer in Japanese real-world clinical practice: Expanded cohort of the SOLUTION study. (March 2022) - Murakami, Haruyasu; Horinouchi, Hidehito; Harada, Hideyuki; Sobue, Tomotaka; Kato, Tomohiro; Atagi, Shinji; Kozuki, Toshiyuki; Tokito, Takaaki; Oizumi, Satoshi; Seike, Masahiro; Ohashi, Kadoaki; Mio, Tadashi; et al.
Highlights: We evaluated treatment practices and outcomes of Japanese stage III NSCLC patients. Chemoradiotherapy was the commonest first-line treatment (46.1% of 744 patients). Median OS and the 3-year OS rate in all patients were 25.4 months and 38.7%. Abstract: Objectives: To evaluate the actual treatment patterns with respective outcomes and the patient characteristics of stage III non-small cell lung cancer (NSCLC) in Japan. Materials and methods: Patients (aged ≥20 years at diagnosis) who were diagnosed with stage III NSCLC between January 2013 and December 2014 and underwent surgery, chemoradiotherapy (CRT), chemotherapy (CT), or radiotherapy (RT) at 11 institutions in Japan were consecutively registered in this retrospective, observational study (SOLUTION; UMIN000031385). Study measures included patient characteristics, first-line treatments, overall survival (OS), progression-free survival, objective response rate, and incidence of radiation-related adverse events. Results: The study population comprised 744 patients. The tumors were classified as stage IIIA and IIIB in 58.9% and 41.1% of patients, respectively. The tumors were considered resectable at diagnosis in 25.0% of patients. First-line treatments were surgery (20.0%), CRT (46.1%), CT (22.2%), and RT (11.7%). The median OS (mOS) in the overall population was 25.4 months and the 3-year OS rate was 38.7%. Among the four first-line treatment cohorts, OS most favored the surgery cohort: mOS was 43.4 months and the 3-year OS rate was 53.8%. Prognostic factors for OS in each treatment modality were analyzed using multivariable analysis and included the following: age, performance status, and histological type for the surgery cohort; sex, histological type, and primary lesion location (lower lobe) for the CRT cohort; and performance status and clinical stage for the RT cohort. The timing of peak incidence of pneumonitis from the start of first-line treatment was 18–20 and 12–14 weeks in the CRT and RT cohorts, respectively. Conclusion: Patients with clinical stage III NSCLC received a variety of treatments selected to the clinical background and tumor status, and we clarified the outcome and prognostic factors. These findings will be a useful reference for future studies evaluating newly introduced treatments for stage III NSCLC.